2022
DOI: 10.1101/2022.10.08.511444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An unbiased screen identified the Hsp70-BAG3 complex as a regulator of myosin binding protein C3

Abstract: Objective: We aim to identify regulators of myosin binding protein C3 (MyBP-C) protein homeostasis. Background: Variants in myosin binding protein C3 (MYBPC3) account for approximately 50% of familial hypertrophic cardiomyopathy (HCM). Most pathogenic variants in MYBPC3 are truncating variants that lead to reduced total levels of MyBP-C protein. Elucidation of the pathways that regulate MyBP-C protein homeostasis could uncover new therapeutic strategies that restore normal protein levels. Method: We developed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…This would potentially accelerate the deterioration of function and progression of disease. As suggested by Thompson et al 1 , approaches that increased BAG3 protein levels or increased its activity could be therapeutically beneficial in these patients. Supporting this hypothesis, we previously found that adeno-associated virus–mediated overexpression of BAG3 was able to rescue sarcomere function in a mouse heart failure model.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…This would potentially accelerate the deterioration of function and progression of disease. As suggested by Thompson et al 1 , approaches that increased BAG3 protein levels or increased its activity could be therapeutically beneficial in these patients. Supporting this hypothesis, we previously found that adeno-associated virus–mediated overexpression of BAG3 was able to rescue sarcomere function in a mouse heart failure model.…”
mentioning
confidence: 93%
“…This is the approach that Thompson et al 1 have taken in this issue of JACC: Basic to Translational Science . The goal of this study was to identify a small molecule that could enhance the level of cMyBPC protein in a model of haploinsufficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the disease is dominant and severe, most MFM6 cases result either from de novo mutation or from inheritance of the mutation from a parent who is a genetic mosaic for the mutation [4,[6][7][8]. Although certain small molecule drugs showed improvements in pre-clinical models [9][10][11][12], there are no effective treatments for MFM6.…”
Section: Introductionmentioning
confidence: 99%
“…Since the disease is dominant and severe, most MFM6 cases result either from de novo mutation or from inheritance of the mutation from a parent who is a genetic mosaic for the mutation [4, 6-8]. Although certain small molecule drugs showed improvements in pre-clinical models [9-12], there are no effective treatments for MFM6. Therefore, we reasoned that advancements in genome engineering may provide alternative routes for effective treatment strategies for MFM6, given its well-known genetic underpinning.…”
Section: Introductionmentioning
confidence: 99%